Preiskave modelov zidanih stavb na potresni mizi - Tomaževič, Miha (Gradbeni vestnik, 2008)
The advantages and disadvantages of testing of small-scale masonry building models on a simple shaking table at ZAG are discussed. The costs of testing are relatively low, compared to the costs of testing large scale models or prototype structures. Phzsical models are cheaper than prototypes, although preliminary studies to develop adequate model materials are most often needed.Except the platform, other testing equipment, such as programmable actuators, steel supporting system, and electronic data acquisition system can be also used for any other types of testing. Since scale effects represent limitations, only the overall seismic behaviour of structural systems can most often be studied, and not the behaviour of structural details. Failure mechanisms of masonry structures subjected to seismic ground motion can be simulated fairly well. The results of tests are used for the verification of numerical models as well as for the determination of values of parameters, which determine the behaviour of masonry structures in the non-linear range of seismic response. Various approaches of testing are discussed and typical examples presented. The basic procedures to model the earthquake ground motionare explained. Instrumentation of models, data acquisition and processing to analyze the dynamic behaviour of tested models are also presented.
Keywords: gradbene konstrukcije; meritve; modeliranje; potresna miza; zidane konstrukcije